AB0624 Interstictial lung disease in scleroderma: severity associated factors. objetives. (15th June 2017) - Cano, D Sanchez; Centeno, N Ortego; Moreno, MT Cruces; Comet, L Sáez; Freire, M; Todlí, JA Parra; Caballeira, M Rodríguez; Aznar, C Simeόn; ,
Abstract : Background: Systemic sclerosis (SSc) can virtually affect any organ system (such as lungs, kidneys, gastrointestinal tract, and heart). However, it is the pulmonary manifestations that account for the majority of deaths, especially interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH). Objectives: Our aim was to assess the differences between severe and mild-to-moderate ILD in SSc. Methods: A descriptive study was performed, using the available data from the Spanish Scleroderma Study Group (RESCLE). ILD was deemed as serious when forced vital capacity (FVC) was <50%. Patients were classified attending the modified classification criteria proposed by LeRoy and Megdsger. Results: Fourteen referral centers for SSc participated in the registry. By April 2014, 1374 patients with SSc had been enrolled, 541 of whom (39.4%) had ILD, which was severe in 72 of them (13.2%). There were no significant differences as far as sex and age at onset is concerned. Patients with diffuse SSc presented with severe ILD more frequently than those with limited SSc (57% vs. 35%, p=0.002), as well as those who had tested positive for ATA (51% vs. 33%, p=0.005). Aditionally, prevalence of FVC<50% was higher in patients with myopathy (32% vs. 15%, p=0.002). Mean FVC was 40.2±6.4 in the severe ILD group, whilst it was 80.3±18.9 in the mild-to-moderate one (p<0.001), and mean DLco was 36.7±15.2 and 62.9±34.5, respectively (p<0.001). Likewise, DLco<70% was also more frequent among patients with severe ILD (100% vs. 69%, p<0.001), as well as mean DLco/VA (56.2±24.2 vs. 74.2±42.0, p=0.002). PAPs was equally higher when FVC<50% (42.2±18.2 vs. 35.1±13.4, p=0.034), and so was the frequency of PAPs>40mmHg (66% vs. 29%, p<0.001) and PAH by right heart catheterism (19% vs. 11%, p=0.050). Finally, by means of a multiple logistic regression, both ATA positivity [OR 0.17 (0.05–0.58), p=0.005] and low DLco [0.93 (0.91–0.95), p=0.000] were found to be related with FVC<50% Conclusions: Patients with ACA positivity and with a limited variant of SSc seem to be at lower risk of severe interstitial lung involvement. Furthermore, the presence of myopathy may contribute to explain the decrease of FVC in SSc patients. References: Steen VD, Medsger TA. Changes in causes of death in systemic sclerosis, 1972–2002. Ann Rheum Dis 2007; 66: 940–4. LeRoy EC, Medsger TA, Jr. Criteria for the classification of early systemic sclerosis. J Rheumatol 2001; 28: 1573–6. Disclosure of Interest: None declared